Cultural Proficiency and Multitasking Behavior: Implications on Librarians’ Job Performance (British Journal of Multidisciplinary and Advanced Studies, 2024)
Librarians who have a strong understanding of cultural differences and who demonstrate multiple task skills properly serve their users’ demands.  This study aimed to determine the level of cultural proficiency and multitasking behavior on the job performance of library and information professionals.  Eighty-five (85) librarians and eighty-five (85) head librarians participated in the study.  In this descriptive-correlational study, a research questionnaire was utilized and the gathered data was subsequently analyzed using descriptive and inferential statistical tools.  The study indicates that librarians’ cultural proficiency and job performance were rated high, suggesting a strong foundation for cultural competence and effective task completion.  Multitasking behavior was rated moderate, indicating a tendency to multitask during deadlines or meetings.  Job performance in task completion, job knowledge, adaptability, and technology adeptness were also very high, suggesting adaptability and openness to learning and trying new approaches.  The study concludes that cultural proficiency and multitasking significantly influence job performance, with involvement in metacognition, cognition, motivation, and behavior leading to more effective task completion, a better understanding of issues, and more innovative ideas at work.  The study underscores that librarians’ high cultural proficiency and moderate multitasking skills significantly enhance their job performance, with their adaptability, willingness to learn, and innovative thinking fostering efficient task completion and a comprehensive understanding of their professional responsibilities.  Future studies might consider investigating the effects of targeted training initiatives designed to boost librarians’ cultural proficiency, multitasking capabilities, and adaptability to ascertain whether such interventions could substantially enhance job performance and task execution efficiency.